2021
DOI: 10.48550/arxiv.2107.10743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ORion Alma New GEneration Survey (ORANGES) I. Dust continuum and free-free emission of OMC-2/3 filament protostars

M. Bouvier,
A. López-Sepulcre,
C. Ceccarelli
et al.

Abstract: Context. The spectral energy distribution (SED) in the millimetre to centimetre range is an extremely useful tool for characterising the dust in protostellar envelopes as well as free-free emission from the protostar and outflow. Actually, the evolutionary status of solar-type protostars is often based on their SED in the near-infrared to millimetre range. In addition, the presence or absence of free-free emission can be considered an indicator of the source evolutionary stage (Class 0/I versus Class II/III). … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Interferometric observations have also found low spectral indices at millimeter wavelengths in the dusty ∼ 60 au disk surrounding L1527, a Class 0/I protostar and in the Class 0 protostar, L1157 (Nakatani et al 2020;Chiang et al 2012). In the Orion region, recent ALMA observations confirmed the low spectral indices of dust emission in 16 protostars at scales < 100 au (Bouvier et al 2021). Analyzing the dust properties of 12 nearby Class 0 protostars observed at 1.3 and 3.2 mm with the PdBI (CALYPSO survey), Galametz et al (2019) found that most Class 0 protostars, sampled from different star-forming regions, show significantly shallow dust emissivities at envelope radii ∼ 100 − 500 au, with β < 1 (see left panel of Figure 14).…”
Section: Observations Of Dust Grain Properties In Embedded Protostarsmentioning
confidence: 87%
“…Interferometric observations have also found low spectral indices at millimeter wavelengths in the dusty ∼ 60 au disk surrounding L1527, a Class 0/I protostar and in the Class 0 protostar, L1157 (Nakatani et al 2020;Chiang et al 2012). In the Orion region, recent ALMA observations confirmed the low spectral indices of dust emission in 16 protostars at scales < 100 au (Bouvier et al 2021). Analyzing the dust properties of 12 nearby Class 0 protostars observed at 1.3 and 3.2 mm with the PdBI (CALYPSO survey), Galametz et al (2019) found that most Class 0 protostars, sampled from different star-forming regions, show significantly shallow dust emissivities at envelope radii ∼ 100 − 500 au, with β < 1 (see left panel of Figure 14).…”
Section: Observations Of Dust Grain Properties In Embedded Protostarsmentioning
confidence: 87%